2008
DOI: 10.1007/s11104-008-9650-0
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of urea N addition on soil microbial community in a semi-arid temperate steppe in northern China

Abstract: Nitrogen (N) addition has been well documented to decrease plant biodiversity across various terrestrial ecosystems. However, such generalizations about the impacts of N addition on soil microbial communities are lacking. This study was conducted to examine the impacts of N addition (urea-N fertilizer) on soil microbial communities in a semi-arid temperate steppe in northern China. Soil microbial biomass carbon (C), biomass N (MBN), net N mineralization and nitrification, and bacterial and fungal community lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
69
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(82 citation statements)
references
References 45 publications
10
69
2
1
Order By: Relevance
“…Previous studies showed that N addition stimulated microbial biomass in grassland or pasture (Rousk and Bååth 2007;Hamer et al 2009). However, decreases in microbial biomass with increasing N application in steppe have also been reported (Zhang et al 2008;Bi et al 2012), which is consistent with our results. The soil acidification caused by N addition in this study was more severe than that experienced in other studies (Magill et al 1997;Lu et al 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies showed that N addition stimulated microbial biomass in grassland or pasture (Rousk and Bååth 2007;Hamer et al 2009). However, decreases in microbial biomass with increasing N application in steppe have also been reported (Zhang et al 2008;Bi et al 2012), which is consistent with our results. The soil acidification caused by N addition in this study was more severe than that experienced in other studies (Magill et al 1997;Lu et al 2009).…”
Section: Discussionsupporting
confidence: 93%
“…5. The data was statistically analyzed by One-way analysis of variance (ANOVA) and followed by Turkey's HSD test 26) at a 95% significance level. Statistical p-value was set to p < 0.05.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Increasing N deposition, precipitation changes, and associated ecological alterations influence the soil microbial communities in various ecosystems; hence, these phenomena will become important topics for future research (Zhang et al 2008;Zak et al 2011). …”
mentioning
confidence: 99%